Selective Formation of an FeIVO or an FeIIIOOH Intermediate From Iron(II) and H2O2: Controlled Heterolytic versus Homolytic Oxygen Oxygen Bond Cleavage by the Second Coordination Sphere - Khaled Cheaib; Katell Sénéchal-David; Christian Herrero; Régis Guillot; Martin Clémancey; Jean-Marc Latour; Sam P. de Visser; Jean-Pierre Mahy; Frédéric Banse; Frédéric Avenier; Muhammad Qadri Effendy Mubarak (John Wiley and Sons Ltd, 2024)
Volume131, Issue3